Wheat and Grain Sorghum in Four-Year Rotations - A. Schlegel; J. D. Holman; C. Thompson (Kansas Agricultural Experiment Station Research Reports, 2015)
Research on 4-year crop rotations with wheat and grain sorghum was initiated in 1996 at the Southwest Research-Extension Center near Tribune, Kansas. Rotations were wheat-wheat-sorghum-fallow (WWSF), wheat-sorghum-sorghum-fallow (WSSF), and continuous wheat (WW). Soil water at wheat planting averaged about 9 inches following sorghum, which is about 3 inches more than the average for the second wheat crop in a WWSF rotation. Soil water at sorghum planting was only about 1 inch less for the second sorghum crop compared with sorghum following wheat. Grain yield of recrop wheat averaged about 80% of the yield of wheat following sorghum. Grain yield of continuous wheat averaged about 65% of the yield of wheat grown in a 4-year rotation following sorghum. Wheat yields were similar following one or two sorghum crops. Similarly, average sorghum yields were the same following one or two wheat crops. Yield of the second sorghum crop in a WSSF rotation was only about 10% of the yield of the first sorghum crop in 2014, although the long-term average is about 65% of the yield of the first sorghum crop.
Keywords: cropping systems; rotations; sorghum; wheat; yield; soil water